2002
DOI: 10.1177/02731602022003003
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Early Adolescents’ Relationship Qualities, Self-Efficacy, and Depression Symptoms

Abstract: Relationship qualities and low perceived social self-efficacy might be associated with early adolescents’depression symptoms and with later gender differences in depression prevalence. Gender comparisons in the means, and associations with depression symptoms of self-rated intimate support, conflict, intimate support self-efficacy, and conflict management self-efficacy were examined for predominantly White community-recruited 12-year-olds (114 boys, 109 girls). Perceived low parental intimate support, high con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 48 publications
9
64
1
3
Order By: Relevance
“…Concurrent associations have been found between conflict and support: adolescents with more conflict with their parents were found to perceive their parents as less supportive (Jenkins et al 2002). Similarly, a study among late adolescents found a significant negative correlation between parental social support and family conflict (Cutrona et al 1994).…”
Section: Development Of Support Conflict and Powermentioning
confidence: 96%
“…Concurrent associations have been found between conflict and support: adolescents with more conflict with their parents were found to perceive their parents as less supportive (Jenkins et al 2002). Similarly, a study among late adolescents found a significant negative correlation between parental social support and family conflict (Cutrona et al 1994).…”
Section: Development Of Support Conflict and Powermentioning
confidence: 96%
“…While some degree of conflict with parents is considered to be normal during adolescence , prolonged, intense and repeated conflict is frequently associated with poor psychological adjustment (Barber & Delfabbro, 2000;Branje et al, 2010;Jenkins et al, 2002;Sheeber, et al, 2007;Vazsonyi & Belliston, 2006). Other negative qualities such as high levels of over-intrusive and authoritarian parental control (Rigby, Slee & Martin, 2007), and low levels of perceived parental communication (Ackard, NeumarkSztainer, Story & Perry, 2006) have also been significantly associated with negative well-being in adolescence.…”
Section: Parental Relationships and Mental Healthmentioning
confidence: 99%
“…Estudos mostram diferenças entre os sexos, em especial quando a autoeficá-cia está relacionada a outros aspectos, como desempenho acadêmico, depressão e aceitação em grupos (Pastorelli, & cols., 2001;Jenkins, Goodness, & Buhrmester, 2002;Vekiri, & Chronaki, 2008). O senso de autoeficácia de crianças pode estar relacionado também à idade, pois, de acordo com Eccles, Wigfield e Schiefele (conforme citado por Costa & Boruchovitch, 2006), crianças com menor idade tendem a apresentar um senso de autoeficácia mais elevado do que os seus pares mais velhos.…”
Section: Introductionunclassified